Incidence and Predictors of Left Ventricular Thrombus After Primary Percutaneous Coronary Intervention for Anterior ST‐Segment Elevation Myocardial Infarction. Issue 10 (10th September 2015) - Driesman, Adam; Hyder, Omar; Lang, Christopher; Stockwell, Phillip; Poppas, Athena; Dawn Abbott, J.
Abstract : Background: The role of warfarin in anterior ST‐segment elevation myocardial infarction (STEMI) complicated by left ventricular (LV) dysfunction in patients treated with primary percutaneous coronary intervention (PCI) and dual antiplatelet therapy is unclear. Warfarin may prevent cardioembolic events but significantly increases bleeding in the setting of dual antiplatelet therapy. Hypothesis: The incidence of LV thrombus in anterior STEMI patients treated with PCI is low, and clinical predictors might be valuable in determining patients at risk. Methods: We performed a retrospective, single‐center study of 687 consecutive patients with anterior STEMI treated with PCI from 2006 to 2013. Baseline variables were evaluated in 310 patients at high risk for LV thrombus based on echocardiographic criteria. Patients with definite, probable, and no LV thrombus were compared by ANOVA, χ 2, or t test where appropriate. Logistic regression analysis was performed. Results: The incidence of LV thrombus was 15% (n = 47 probable/definite thrombus). Cardiac arrest was the only independent characteristic associated with increased risk of LV thrombus (odds ratio [OR]: 4.06, 95% confidence interval [CI]: 1.3‐12.7). Trends were observed for a lower risk in cardiogenic shock (OR: 0.33, 95% CI: 0.10‐1.05) and aspirin use at baseline (OR: 0.43, 95% CI: 0.17‐1.1). Treatment variables associated with LV thrombus included unfractionated heparin use post‐PCI (OR: 2.43, 95% CI: 1.16‐5.1) and use of balloon angioplasty without stent. Conclusions: In contemporary practice with primary PCI, definite LV thrombus following anterior STEMI with LV dysfunction is challenging to predict. Further investigation is needed to determine if there is a subset of patients that should be treated with prophylactic warfarin.